Pharmacodynamic target associated with clinical outcome of hospital-acquired pneumonia treatment with cefoperazone/sulbactam - Narawadeeniamhun (2018)
Background: For anti-infective agents, pharmacodynamics (PD) parameters have been proposed as predictors of clinical and microbiological success. Hospital-Acquired Pneumonia (HAP) patients have altered pharmacokinetics (PK) that needs to be considered when dosing antibiotics. We conducted a prospective study to assess (PK/PD) of cefoperazone/sulbactam treatment in HAP patients and to identify patient and PD indices associated with clinical response. Methods: Patients with HAP were identified, and information related to patient demographics, clinical status, antibiotic treatment and clinical outcome were documented. Cefoperazone/Sulbactam plasma concentrations were analyzed by validated High-Performance Liquid Chromatography (HPLC).Patient characteristics and PK/PD related factors were tested for associations with clinical outcome. Results: Twenty eight patients of hospital-acquired pneumonia patients were identified. 26 patients (93.1%) had Acinetobacterbaumannii infection and 2 patients (6.9%) had both of Pseudomonas aeruginosa and Acinetobacterbaumannii infection. At the end of treatment, clinical cure was note in 25 % of patients (7/28), improvement 46.4% (13/28) and 28.5% (8/28) had clinical failure. For microbiology outcome, microbiological eradication was note in 12 /28 (42.9%), 12/28 (42.9%) patients had organism persistence and 4 (14.3%) patients had new infection organism.The time which total cefoperazone concentration exceed the MIC (50% T>MIC) and age of the patient who was less than 60 years were significantly associated with clinical response (p<0.05) Conclusion: The percent of a dosing interval in which thecefoperazone serum concentration is above the MIC (%T>MIC) is strongly associated with clinical outcomeand is essential to the appropriate management of A.baumanii and P.aeruginosa infections.